The Effect of Initial Intensity of Light Sources on the Fraunhofer Diffraction Pattern for Circular Apperture Using the Gauss-Legendre 4 Point Quadrature Integration Numerical Method: Scientific and Islamic Integration-Interconnection - Yanuarief, Cecilia (Kaunia: Integration and Interconnection Islam and Science Journal, 2020)
Visualization of Fraunhofer diffraction pattern of circular apperture has been obtained using the 4 point Gauss-Legendre Quadrature  integration method. The 4 point Gauss-Legendre quadrature integration method is used to solve the integral function of intensity. The intensity function is used to display the intensity distribution of the Fraunhofer diffraction pattern of circular apperture in a visual form through a computer programming simulation based on GUI (Graphycal User Interface) MATLAB. Simulation results show changes in initial intensity affect diffraction patterns.